Vaccine Acceptance, Knowledge, Attitude and Practices Regarding the COVID-19 Pandemic: Cross-Sectional Study among Dentists in Trinidad and Tobago - Reisha Rafeek; Bidyadhar Sa; William Smith (MDPI AG, 2023)
Background: This study's aim was to assess Trinidad and Tobago dentists' vaccine acceptance, knowledge, attitude and practices regarding the COVID-19 pandemic. Methods: All dentists registered with the Trinidad and Tobago Dental Association were invited to complete an online anonymous questionnaire between June and October 2021. Results: A total of 46.2% of dentists responded. The majority of respondents had excellent knowledge of COVID-19 (94.8%), use of personal protective equipment (98.7%) and N95 masks (93.5%), but had poor knowledge about the reuse of N95 masks (27.5%). A total of 34.9% were comfortable providing emergency care to positive or suspected cases of COVID-19, and 64.5% were afraid of becoming infected from a patient. PPE usage was reported at 97.4% and 67.3% for N95 masks. All surfaces of waiting areas were disinfected every 2 h by 59.2%. A total of 90.8% agreed to be vaccinated straight away if a vaccine were made available. Conclusion: Dentists in Trinidad and Tobago have good levels of knowledge, attitude, practices regarding COVID-19. Dentists also have high levels of vaccine acceptance and can play a role in advocating for the COVID-19 vaccine.